New Methods for Numerical Simulation of Welding of Large Thin Structures - Faure, Frédéric; Bergheau, Jean-Michel; Leblond, Jean-Baptiste; Souloumiac, Bruno (European Journal of Computational Mechanics, 2004)
Welding of thin structures often leads to distortions that must be controlled. Whereas numerical simulation of small structures is relatively easy, severe difficulties are encountered in the simulation of large ones. Indeed the mesh must be considerably refined in the heat affected zone, and this leads to huge simulations and prohibitive computation times. Three alternative methods are presented here to circumvent this problem. The first one consists of using only shell elements. The second method consists of using shell elements far from the heat source and a mobile local 3D mesh close to it. The third method is a “local/global” approach which consists of first performing a local 3D simulation of a short portion of the welding bead, and then introducing inelastic strains into some global shell simulation of the full structure. These methods are critically assessed by comparing their results to those of a full 3D simulation in the typical case of a welded plate.